Juventude e política: a participação dos movimentos coletivos e as repercussões nas manifestações de 2013 - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The objetiv of this work was to elaborate a text that discuss about the protests that occurred in 2013, formed by collective actions, that incited a plurality of demands origined, especially, by the articulation and mobilization of the youth. These individuals wach their claims regarding changes in the contexts of public policies. To achieve these objectives, we used bibliographic research, following the parts: a) identification: it was to the phase of identification of the subjects pertinent to the topic under study; b) location and compilation: the bibliographical survey was carried out, with the identification of texts that are interesting, and the location of the texts (mostly scientific articles, monographic products, books and narrative material, text and video) ); c) resumen: the average that was being listed the reference sources, the facts were compiled; d) analysis and interpretation: consisted in the critical analysis of the material listed. Among our foundations were Gohn (2014, 2015), Fleury (2015), Figueiredo (2014), Buzzeto (2013), Cerri (2001), Oliveira (2015), Rosenfield (2014) among many others. We note that among the claims, the most important are those related to public transport, mainly carried out by the MPL and other groups that, to a certain extent, influenced and shaped the protests, such as Black Bloc and the Media Ninja. We verified also that the demand for public transportation was the tip of the bill for discussions on citizenship and democracy, regarding non-compliance with laws, the lack of public policies and ethics in politics, and its representatives.
Youth and politics: the participation of collective movements and the repercussions on the events of 2013
Keywords: Movimentos coletivos; Juventude; Manifestações de 2013; Democracia; Collective movements; Youth; Manifestations of 2013; Democracy; CIENCIAS HUMANAS::HISTORIA